High Stop Band Rejection for Ceramic Loaded Waveguide Filters - Afridi, S. (Institute of Electrical and Electronics Engineers Inc., 2020)
This Paper describes the design procedure of a compact narrowband ceramic loaded filters with wide out of band response. The idea of loading the waveguide filter resonators with ceramic TEM blocks and ceramic ridge blocks are presented. Resonator loading with silver plated transverse electromagnetic (TEM) hole and silver plated ridge ceramic blocks offers wide spurious free bandwidth 2.45 times of center frequency. Simulated and measured results of six pole chebyshev Ceramic ridge loaded filter and simulated results of Ceramic TEM loaded filter are presented in this paper showing excellent out-of-band performance. Â© 2013 IEEE.